A new fossil inchworm moth discovered in Miocene Dominican amber (Lepidoptera: Geometridae). (December 2022) - Sarto i Monteys, Victor; Hausmann, Axel; Solórzano-Kraemer, Mónica M.; Hammel, Jörg U.; Baixeras, Joaquín; Delclòs, Xavier; Peñalver, Enrique
Abstract: We report a fossil geometrid moth, a male, virtually complete, preserved in a clear piece of Miocene Dominican amber dating from 19 to 16 Mya. Fore- and hindwings appear partially overlapped, and all body characters are visible externally in dorsal and ventral views, including the outer surface of the valvae of the genitalia. The scale pattern on the wing membrane is preserved, whereas the wing color pattern is not. It belongs to the genus Dolichoneura (Geometridae: Desmobathrinae) and is named Dolichoneura jorelisae Sarto i Monteys, Hausmann, Baixeras and Peñalver sp. n., based on wing features. Because of the poor fossil record of lepidopterans, both in amber and compression rocks, the description of the available well-preserved specimens is of considerable interest for phylogenetic studies. Furthermore, it could also serve for calibrating molecular clocks and for paleobiogeographic inferences.